EDUKASI DAN PENANGANAN FISIOTERAPI UPAYA SWAMEDIKASI PENYAKIT OSTEOARTHRITIS PADA LANSIA DI POSYANDU KRESNA DESA BEDALI-LAWANG - Novita Lorenza; Tri Noor Cahyo Widodo; Siti Ainun Ma'ruf; Nadya Setyarini Farizka (LPPM Universitas Abdurrab, 2023)
Background : In carrying out daily activities, of course, it requires good body health, but with age the body's health condition decreases which is prone to problems, one of which is osteoarthritis. Osteoarthritis is a cartilage disorder characterized by cartilage degeneration and reduced synovial fluid in a joint which eventually causes joint stiffness, swelling, pain, and limited mobility. Objective : The counseling was held aimed at providing education to the elderly about cases of osteoarthritis, especially about the definition, symptoms, causes, prevention and benefits of active and active resisted exercise at home to reduce complaints of elderly people with osteoarthritis. Research methode : The method used is to provide health education about osteoarthritis to the elderly by using leaflets as a media for counseling, giving pre-test and post-test in the form of questions to the elderly in order to measure the effectiveness of the education provided. Result : The counseling went smoothly and in the evaluation results there was an increase in the knowledge of the elderly from 20% to 100% after being given education. The outreach activities that have been carried out at the Elderly Posyandu â€œKRESNAâ€, RW 11-Bedali Indah, Ds. Bedali, Lawang, Malang can increase the knowledge and insight of the elderly about osteoarthritis and how to prevent and treat osteoarthritis independently by doing active exercise and active resisted exercise.